World Model in the Novel “One Day in the Life of Ivan Denisovich” by A.I. Solzhenitsyn - Kondrateva, Viktoriya (Slavica, 2020)
The paper deals with the world model and ways of its creation in a novel “One Day in the Life of Ivan Denisovich” by A.I. Solzhenitsyn. In the process of world-modeling following basic categories are of a great importance: native-strange, light-darkness, principle of 3 levels. The space of camp is characterized by features of a strange world. Native world is narrowed to the boundaries of hut, bed and even to a hole in a mattress. World organization is also realized with the help of a system of prototypical images, e.g. a table, bread, sun, a stove, etc. Due to this concepts, which have hierarchic values, are formed. Solzhenitsyn achieves generalization following a peculiar way of depicting of a group of characters which can be conditionally called “convicts”. There we can see different social layers, nationalities, ages. It has metonymical nature: according to the principle “a part of the whole” the fate of the entire country is shown. In terms of sense complex “human-being – environment – their interaction” the world model in A.I. Solzhenitsyn’s novel has “human”, natural and social levels in its structure. The writer compresses time and space, satiates it with details, which are different in semiotic power of generalization, and as a result he receives solid world model.